Political Authority, Personal Autonomy and Higher Education - Martin, Christopher (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
Does the liberal state have a role in helping mature citizens make worthwhile educational choices? The question has clear relevance for the aims of higher education in a liberal democratic society. As systems of higher education internationalize, it has become difficult for liberal states to steer high education policy in directions that serve civic interests. This is, in part, because political liberalism imposes restrictions on what one might call directive educational authority: the power to direct citizens toward specific kinds of knowledge, understanding and skills in the interests of making their lives better. This restriction follows from the view that citizens have the capacity to make thier own decisions about how best to live, including decisions about the kind of education they need. My aim in this paper is to make the case for a more direct role for the state in promoting a good life through higher education. In particular, I argue that the liberal state’s obligation to promote autonomy across its citizenry confers legitimate educational authority over post-compulsory, as well as compulsory, education. This argument affirms the State’s educational obligations to citizens beyond a basic or compulsory education. Getting in the way of this affirmation, however, is an overly restrictive account of educational authority that occludes these obligations under the guise of respect for autonomy. Accordingly, in making my case I propose an autonomy-based account educational authority derived from Joseph Raz’s Service Conception, defending this account against the charge that such authority is illegitimately paternalistic.